Digital switchover in Taiwan - Bonnie Peng (International Telecommunications Society (ITS), 2013)
The purpose of this paper is to examine the process of the switchover in Taiwan, the technical standards, legal considerations, resistance from industry and the detailed plan to close analogue signals before the due day. When most technologically advanced countries around the world closed their analogue signals and embraced digital television, Taiwan followed suit and asked terrestrial stations to got digital before the opening of 2012 London Olympic Games. The government in Taiwand believed that the deployment of terrestrial digital infrastructure, the supply of affordable reception equipment (set-top boxes) and marketing campaigns to stimulate consumer demand would ensure the digital switchover would be a success. It could be concluded that, technically, the digital switchover went smoothly. But there's no digital dividend spectrum vacuumed and designed for future use
Keywords: 330; digital switchover; digital dividend